Feeding wet distillers grains plus solubles with and without a direct-fed microbial to determine performance, carcass characteristics, and fecal shedding of Escherichia coli O157:H7 in feedlot heifers - Wilson, B. K.; Holland, B. P.; Step, D. L.; Jacob, M. E.; VanOverbeke, D. L.; Richards, C. J.; Nagaraja, Tiruvoor G.; Krehbiel, C. R. (My University, 2016)
The inclusion of wet distillers grains plus solubles (WDGS) in feedlot diets has become a common practice in many regions of the United States due to the expanded production of byproducts and fluctuating corn prices related to ethanol production and other factors. In addition, societal concerns over the continued use of antimicrobials in agriculture production combined with an enhanced interest in disease and pathogen prevention in the food supply have led to an increased interest in use of direct-fed microbials (DFM) in growing and finishing cattle. Direct-fed microbials have been shown to improve ADG and feed efficiency, alter ruminal fermentation, and decrease fecal shedding of potential harmful pathogens in feedlot cattle in some experiments. The objective of this experiment was to evaluate the effects of WDGS inclusion with or without a DFM containing Lactobacillus acidophilus (1 x 10(6) cfu . heifer(-1) . d(-1)) combined with Propionibacterium freudenreichii (1 x 10(9) cfu , heifer(-1) . d(-1)) on the performance, carcass characteristics, and Escherichia coli O157:H7 shedding in feedlot heifers. In early August, 288 crossbred heifers (initial BW = 295 +/- 28 kg) were assigned to 1 of 4 treatments (12 pens per treatment; 6 heifers per pen) in a randomized complete block design with a 2 x 2 factorial arrangement of treatments. Body weights and fecal grab samples were obtained at approximately 28-d intervals throughout the experiment. Across the feeding period, heifers fed 30% WDGS tended (P = 0.09) to have greater ADG and had greater carcass-adjusted ADG (P = 0.05) compared with heifers fed dry-rolled corn (DRC). Dry matter intake was not affected (P = 0.65) by diet, although carcass-adjusted G:F tended (P = 0.10) to be improved for heifers fed WDGS. Heifers fed 30% WDGS tended (P <= 0.10) to have greater fat thickness at the 12th rib, lower marbling scores, and higher yield grades. The inclusion of L. acidophilus combined with P. freudenreichii in the diet had no effect (P > 0.10) on performance or carcass merit in the present experiment. The incidence of E. coli O157:H7 throughout the experiment was low, with only 18 positive samples across all sampling periods. Neither WDGS inclusion nor the inclusion of L. acidophilus combined with P. freudenreichii in the diet had any effect (P > 0.10) on E. coli O157:H7 shedding in this experiment. Feeding 30% WDGS to feedlot heifers improved animal performance compared to the DRC-based control diet.
Citation: Wilson, B. K., Holland, B. P., Step, D. L., Jacob, M. E., VanOverbeke, D. L., Richards, C. J., . . . Krehbiel, C. R. (2016). Feeding wet distillers grains plus solubles with and without a direct-fed microbial to determine performance, carcass characteristics, and fecal shedding of Escherichia coli O157:H7 in feedlot heifers. Journal of Animal Science, 94(1), 297-305. doi:10.2527/jas2015-9601
Keywords: Beef Cattle; Direct-Fed Microbials; Lactobacillus Acidophilus; Propionibacterium Freudenreichii; Wet Distillers Grains Plus Solubles; Finishing Beef Steers